Penggunaan Abu Vulkanik Sinabung Terhadap Stabilitas Campuran Aspal Beton (Hot Mix) - Sitohang, Oloan; Sinuhaji, Silvia (Fakultas Teknik Universitas Katolik Santo Thomas, 2018)
Mount Sinabung located in Karo regency North sumatera has continuously been erupting since 2010, generating vast amount of waste in the form of volcanic ash. This research aims to investigate the feasibility of utilizing this volcanic ash in asphalt mixture. We used volcanic ash to replace the conventional filler material from stone crush. Sinabung volcanic ash has lower specific gravity,therefore could fill more void in the asphalt mixture, which can affect the value of Marshall test criteria. Asphalt mixture in this study uses the procedure of Hot Mix Asphalt with mixing temperature ranging from 135°C - 150°C. The result shows that the use of Sinabung volcanic ash is feasible to replace the conventional stone crush filler material in these conditions: optimum asphalt content is 6.85%; percentage of volcanic ash-stone ash 50%-50%. According to national standards issued by Bina Marga of Ministry of Public works, the following values comply with the required value. Bulk density density 2.416 kg/cm3, air void 4.724%, Void in Mineral Aggregat 18.667 Void Fillet withAsphalt 74.706%, stability 1000,992 kg, Marshall quotient 3.132 kN/mm, and flow 3.133 mm.